Molecular characterization and phylogenetic analyses of the mitogenome of Wan-Xi white goose, a native goose breed in China - Lunbin Xia; Shaoshuai Bi; Yafei Zhang; Cunwu Chen; Naidong Chen (BMC Genomic Data)
Abstract Background The Wan-Xi white goose (WXG), an indigenous Chinese waterfowl (Anserini: Anserinae), is crucial for goose germplasm conservation. This study aimed to sequence and analyze the complete mitochondrial DNA (mtDNA) of WXG using the BGISEQ-500 platform. The mtDNA's structure and function were investigated to gain insights into its genetic diversity and population structure. Results The mtDNA was found to be 16,743 bp long and comprised 22 transfer RNA (tRNA) genes, 2 ribosomal RNA genes, a complement of 13 protein-coding genes (PCGs), as well as a single noncoding control region known as the D-loop. Notably, all tRNA genes, except for trnS1-tRNA which lacked the dihydrouridine stem, were predicted to adopt the typical cloverleaf structure. Given the genetic variability across the mtDNA of Anser spp. and the intergenic gaps identified by codon analysis, the codon usage patterns were comprehensively examined via comparative analysis of the mtDNAs of WXG and 24 other Anser spp. The relative synonymous codon usage (RSCU) values of the 13 mitochondrial PCGs of WXG were consistent with those of the mitochondrial PCGs of the 24 other Anser spp. Analysis of the neutrality (GC3-GC12), the effective number of codons (ENCs)-GC3, and parity rule 2-bias plots further revealed that natural selection emerged as the primary factor influencing codon bias in Anser sp. High nucleotide diversity (Pi > 0.02) was observed in several regions, including the D-loop, ATP6, 12S rRNA, ND1, 16S rRNA_ND1, COX2, and ND5. Furthermore, the results of nonsynonymous (Ka)/synonymous (Ks) analysis of the 13 mitochondrial PCGs of the 25 species under Anser revealed that the genes were subject to strong purifying selection. The findings of phylogenetic analysis further revealed that WXG and 10 other members of Anser cygnoides clustered into a single branch to form a monophyletic group. Conclusion This research provides valuable insights into the mtDNA of WXG, highlighting its genetic diversity and population structure. The identified mutation hotspots and purifying selection on mitochondrial PCGs suggest potential areas for future research on Anser cygnoides. The findings contribute to our understanding of this rare species and its conservation efforts.